1981
DOI: 10.1111/j.1474-8673.1981.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

The Response of the Costo‐uterine Muscle of the Rat to Adrenoreceptor Agonists During the Oestrous Cycle: A Comparison With the Uterine Horn

Abstract: Adrenoreceptors in the rat costo‐uterine muscle were compared with those in the uterine horn. The responses of electrically‐stimulated preparations of both tissues to isoprenaline and phenylephrine were investigated in the absence and presence of phentolamine and propranolol to block α‐ and β‐adrenoreceptors respectively. Preparations were taken from rats at known stages of the four‐day oestrous cycle. Both adrenoreceptor agonists consistently inhibited contractions in both tissues; threshold sensitivity to is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…As we have shown previously (Hartley & Pennefather, 1981;1984a), preparations responded regularly to electrical field stimulation for periods of 5-6 h. All amines used produced only inhibition of electricallyevoked contractions. Figure 1 shows the inhibitory effects of fenoterol and adrenaline upon evoked-contractions of costo-uterine muscle preparations.…”
Section: Isolated Organ Bath Studiessupporting
confidence: 68%
See 3 more Smart Citations
“…As we have shown previously (Hartley & Pennefather, 1981;1984a), preparations responded regularly to electrical field stimulation for periods of 5-6 h. All amines used produced only inhibition of electricallyevoked contractions. Figure 1 shows the inhibitory effects of fenoterol and adrenaline upon evoked-contractions of costo-uterine muscle preparations.…”
Section: Isolated Organ Bath Studiessupporting
confidence: 68%
“…Both phenylephrine and isoprenaline reduced the size of contractions. These effects were unaffected by phentolamine but were antagonized though not reversed by propranolol (Hartley & Pennefather, 1981). We, therefore, suggested that the adrenoceptors within the tissue are exclusively of the ,-type.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…The rat costo-uterine muscle connects the tuba1 end of the uterine horn to the lower ribs (Gabella 1976). Studies with field-stimulated (Hartley & Pennefather 1981 and carbacholcontracted (Henry et al 1984(Henry et al , 1985 preparations have established that this smooth muscle contains adrenoceptors solely of the &subtype which mediate physiological antagonism of contrac-tile stimuli. These P,-receptors are efficiently coupled to the processes mediating inhibitory effects, since the &adrenoceptor selective agonists noradrenaline and R0363 [( +)-1-(3,Cdimethoxyphenethylamino)-3-(3,4-dihydroxyphenoxy)-2-propanol oxalate] (Raper et al 1978;Iakovidis et al 1980), produce full inhibition of electrically evoked contractions, and are blocked selectively by the P2-adrenoceptor antagonist, ICI 118,551 .…”
Section: Introductionmentioning
confidence: 99%